BOPAM’s Bright and Dark Excited States: Insight from Structural, Photophysical, and Quantum Chemical Investigations - Kexin Yu; Thanh Chung Pham; Jianjun Huang; Yixuan Li; Luc Van Meervelt; Mark Van der Auweraer; Daniel Escudero; Wim Dehaen (Molecules, 2025)
BOPAM exhibits high fluorescence quantum yields, along with exceptional photostability, rendering it a promising platform for applications as fluorescence sensors. However, the development of BOPAM-based fluorophores with extended emission wavelengths remains limited, and the underlying mechanisms of fluorescence quenching via the population of dark twisted intramolecular charge transfer (1TICT) excited states are not yet fully understood. To address these gaps, we synthesized a series of BOPAM derivatives by incorporating electron-donating groups at the boron atoms and the phenyl rings of the BOPAM core. The introduction of bromide, phenyl, and naphthyl groups preserved the intrinsic locally excited (1LE) emission of BOPAM. In contrast, the incorporation of diphenylamine (BP-DA) and triphenylamine (BP-TA) moieties resulted in a red-shifted emission, attributed to an enhanced intramolecular charge transfer (ICT) process. Notably, in acetonitrile, BP-DA exhibited weak fluorescence originating from a 1TICT state, which was populated via the S2 → 1TICT transition. Furthermore, the emission observed from BP-TA was associated with a higher-lying excited state, likely the initially populated S2 state possessing a 1LE character. These findings not only introduce novel red-emissive BOPAM-based fluorophores, but also offer valuable insights into the role of the S2 state in governing fluorescence quenching mechanisms in BOPAM derivatives.